Emerging infectious diseases in free-ranging wildlife-Australian zoo based wildlife hospitals contribute to national surveillance. - Keren Cox-Witton; Andrea Reiss; Rupert Woods; Victoria Grillo; Rupert T Baker; David J Blyde; Wayne Boardman; Stephen Cutter; Claude Lacasse; Helen McCracken; Michael Pyne; Ian Smith; et al. (PLoS ONE)
Emerging infectious diseases are increasingly originating from wildlife. Many of these diseases have significant impacts on human health, domestic animal health, and biodiversity. Surveillance is the key to early detection of emerging diseases. A zoo based wildlife disease surveillance program developed in Australia incorporates disease information from free-ranging wildlife into the existing national wildlife health information system. This program uses a collaborative approach and provides a strong model for a disease surveillance program for free-ranging wildlife that enhances the national capacity for early detection of emerging diseases.